The Correlation of Sales Growth, Liquidity, and Asset Growth with Capital Structure in Food and Beverage Companies - Silvia, Rina; Meti, Yonas (International Journal of Social Science and Business, 2020)
This study aims to analyze the factors that influence the capital structure of food and beverage companies. The variables used in this study are sales growth, liquidity, asset growth and capital structure. The population of this study were all food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2019 period, totaling 29 companies. The sample was selected by means of a purposive sampling method. There were 20 companies that met the criteria as research samples so that the research data amounted to 60. The data analysis techniques used were descriptive statistical analysis, classical assumption test, and multiple linear regression. Based on the results of data analysis, the calculated F-count is 4.770 with a significance of 0.005, the significance value is smaller than 0.05. It is concluded that Sales Growth has no positive effect on capital structure. Liquidity has a negative effect on capital structure. Asset growth has no positive effect on capital structure.